Chapter Smart Specialisation Strategies as Drivers for (Smart) Sustainable Urban Development - Trillo, Claudia (InTechOpen, 2016)
The place-based approach is at the forefront of the current European cohesion policy reform. The Smart Specialisation Strategy (S3) boosts economic development through research and innovation. It is built on place-based areas showing higher potential for growth. Although S3 is deeply rooted in the uniqueness of the place, its implementation is still far from being clearly spatial-led. The research programme MAPS-LED (Multidisciplinary Approach to Plan Smart specialisation strategies for Local Economic Development), financed by RISE-Horizon 2020, aims at filling this gap. This chapter discusses a novel concept developed with the aim to incorporate a spatial component in the innovative urban clusters, e.g. the urban pattern as cognitive infrastructure for S3. The preliminary findings from the case study of Kendall Square, a former brownfield located in Cambridge (MA), in close proximity with the Massachusetts Institute of Technology, led to conclude that it is essential to complement S3 implementation with spatial interventions in the built environment to create a physical ecosystem supportive of innovation, including: shared facilities and private small businesses facilitating interaction; public services and facilities that allow preserving uniqueness of the place and inclusiveness. Furthermore, the spatial pattern has to be supportive of a walkable and dense environment.